ASSESSMENT OF HEMATOLOGIC INDICES AND THEIR CORRELATION TO HEMOGLOBIN A1C AMONG BOSNIAN CHILDREN WITH TYPE 1 DIABETES MELLITUS AND THEIR HEALTHY PEERS - Tihić-Kapidžić, Suzana; Čaušević, Adlija; Fočo-Solak, Jasmina; Malenica, Maja; Tanja, Dujić; Babić, Nermina; Hasanbegović, Sniježana; Begović, Ermin (Journal of Medical Biochemistry, 2020)
Background: Altered level of many hematological parameters have been directly associated with diabetes in adults, while studies on children with type 1 diabetes mellitus are lacking. The aim of this study was to determine hematological indices in diabetic Bosnian children in comparison to healthy controls as well as to correlate their levels to blood glucose and hemoglobin A1c. Methods: 100 healthy and 100 children with type 1 diabetes mellituss (age 1-18 years) were included in this study. Complete Blood Count, Hemoglobin A1c and glucose were tested. Results were analysed by IBM SPSS Statistics version 23. Results: Significant differences (p<0.05) between healthy and diabetic children were found in HbA1c, glucose, Mean Platelet Volume, number of white blood cells and erythrocytes, hematocrit, hemoglobin and MCH values. No gender differences or significant age differences were seen for hemoglobin, hematocrit and MCV, while platelets, MPV and MCH differed by age only in healthy children. When diabetic children were classified according to HbA1c levels, significant differences were seen for erythrocyte count and hematocrit value (p=0.013 and 0.019 respectively). Number of erythrocytes and white blood cells correlated significantly with HbA1c (p=0.037 and 0.027 respectively). Conclusion: Lower levels of erythrocytes, hematocrit and hemoglobin in diabetic compared to healthy children indicate possible development of anemia, while higher MCV, MCH and MPV values indicate alteration in erythrocyte morphology. Hematological indices could be useful inexpensive tool in diagnosis and follow up of type 1 diabetes in children.